Bob books. Sight words kindergarten - Kertell, Lynn Maslen (Scholastic, 2010)
"Sight words are common words that appear again and again in your children's reading material. Bob Books Sight Words Kindergarten uses repetition and fun stories to introduce important sight words. Consistent short vowels and simple stories ensure that each book is a gentle step into early reading. Inside you'll find: 10 easy-to-read, hilarious books ; 30 two-sided flash cards. 30 new sight words--3 introduced in each story. Context clues and illustrations to give sight word hints. Consistent short vowels for easy decoding in the rest of the story"--p. [4] of container.